Identifying and Assessing Health, Safety and Environmental hazards of Safety Shoe Industry - Abdollah MOHAMADI; Sama KARIMI; Elham KARIMI (بهداشت کار و ارتقای سلامت, 2022)
Introduction: Despite increasing advances, various industries are still involved in various accidents caused by Health, Safety, and Environment (HSE) risks. These accidents, in addition to human and environmental damage, impose high economic costs. Accordingly, risk identification in order to prevent losses and Unfavorable results of events are performed. Therefore, the health, safety and environmental hazards of the safety shoe industry were identified and evaluated. Methods: This descriptive study was conducted, in 2020, in one of the safety shoe industries using Failure Modes and Effects Analysis technique (FMEA). The FMEA team was first formed to collect the required information, and then, the potential hazards were identified and recorded. Then, the Risk Priority Number (RPN) was obtained by multiplying the three factors of risk severity, occurrence and detection. Finally, modifications were proposed for unacceptable risks. All calculations were performed by Excel. Results: In 204 risks were identified 40 potential hazards with RPN from 108 to 300 and 164 potential hazards with RPN from 12 to 100 were identified. Gas with RPN= 300 and accumulation of explosive gases and vapors with RPN= 270 and electricity with RPN= 252 also inadequate lighting had the lowest RPN of 12. Conclusion: The results of the present study show that FMEA is an appropriate method for identifying risks and assessing the risk of devices, equipment and machinery in the footwear industry that can identify and prioritize existing potential hazards.